Anomalia anatômica da veia porta: uma causa rara de impossibilidade de doação do lobo direito em transplante hepático intervivos - Freitas,Alexandre Coutinho Teixeira de (2006)
Living related liver transplantation is being increasingly used for patients that can not wait for a cadaveric organ. We describe a case of a right lobe donor who had a type III portal vein anomaly. On this anomaly the portal vein gives branches first to the right posterior vein and then to the right anterior vein and the left portal vein. The recipient had portal vein thrombosis that was recognized only during the surgery. The Doppler examination performed before the operation did not detect this thrombosis. The transplant was not accomplished. Anatomical anomaly of the portal vein may be a rare cause impossibility to organ donation in living related liver transplantation.